Antibiotics administration alleviates the high fat diet‐induced obesity through altering the lipid metabolism in young mice. Issue 1 (17th October 2022) - Luo, Shiyue; Zhang, Hongyang; Jiang, Xuejun; Xia, Yinyin; Tang, Shixin; Duan, Xinhao; Sun, Wei; Gao, Min; Chen, Chengzhi; Zou, Zhen; Zhou, Lixiao; Qiu, Jingfu
Abstract: Currently, there is a global trend of rapid increase in obesity, especially among adolescents. The antibiotics cocktails (ABX) therapy is commonly used as an adjunctive treatment for gut microbiota related diseases, including obesity. However, the effects of broad‐spectrum antibiotics alone on young obese hosts have rarely been reported. In the present study, the 3‐week‐old C57BL/6J male mice fed a high‐fat diet (HFD) were intragastric administration with ampicillin, vancomycin, metronidazole or neomycin for 30 days. The lipid metabolites in plasma were assessed by biochemical assay kits, and genes related to lipid metabolite in the white adipose were assessed by qPCR. To further analyze the underlying mechanisms, the expression of genes related to lipid metabolism, inflammatory reactions and oxidative stress in the liver were determined by qPCR assay. In addition, the expression of oxidative damage‐associated proteins in the liver were detected by western blot. The results showed that oral antibiotics exposure could reduce body weight and fat index in HFD‐fed mice, concurrent with the increase of white adipose lipolysis genes and the decrease of hepatic lipogenic genes. Furthermore, antibiotics treatment could clearly reverse the HFD‐induced elevation of oxidative damage‐related proteins in the liver. Together, these findings will provide valuable clues into the effects of antibiotics on obesity.